Morbidity Pattern and Association of Hospital Stay With the Outcome Of Severely Asphyxiated Newborn in a Tertiary Care Hospital (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Perinatal asphyxia is a prime causality of death and disability among newborns in less developed countries like Bangladesh. Few studies were made to report information on this neonatal situation in our country because of limitations. It aims to assess clinical problems and associated hospital stays concerning outcomes in severely asphyxiated babies.Materials and methods: It was a cross-sectional study, done in the Neonatal Ward, Department of Pediatrics, Chittagong Medical College Hospital, Chattogram from 1 st December 2013 to 31 st  May 2014. This study includeda totalof 100 asphyxiated newborns. All the relevant data were evaluated,compiled and statistical analyses were done.Results: Out of 100 neonates, the ratio of male (66%) and female (34%) was 1.9:1. 60% of babies were admitted to this hospital within 12 hours of age. Most of the babies admitted were not born in this hospital (66%). More than half of neonates were born by Lower Uterine Caesarian Section (LUCS)(54%). Among them, preterm deliveries were 36% and Low Birth Weight (LBW) neonates were 48%. This study showed various morbidities in studied cases, in which Hypoxic Ischemic Encephalopathy (HIE) was most common (78%) and others were respiratory distress (30%), convulsion (26%) included HIE and other causes like hypoglycemia, hypocalcemia, septicemia (22%), apnea (18%), feeding intolerance (14%) excluding Necrotizing Enterocolitis (NEC) and due to other causes like septicemia, NEC (10%), hyperbilirubinemia (8%). Out of 100 neonates 38 (38%) died. In this study, most of the deaths were associated with LBW (63.2%), prematurity (47.4%), HIE (89.5%) respiratory distress (30%) and sepsis (22%). This study showed that 90.3% of newborns stayed in the hospital for 1-2 weeks among the survivors. The majority (42.1%) of deaths were within 1st week.  Conclusion: Among the serious neonatal complications, HIE was the most common in asphyxiated neonates, and mortality was higher in neonates with HIE. Besides neurological manifestations, respiratory distress, and septicemia, apnea is also a major contributor to the morbidity as well as associated mortality of severely  asphyxiated babies. Adequate antenatal, intrapartum, and  neonatal care with the use of sophisticated technology will improve the neonatal outcome.JCMCTA 2023 ; 34 (2) : 79-84